2006
DOI: 10.1080/00140130600667444
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gait kinematics and posture with the use of a front pack

Abstract: The objective of this study was to determine if posture during gait can be affected by position of the load. It was hypothesized that the front pack would result in postural changes in the gait cycle, compared to a similarly loaded backpack. Thirteen healthy adults, free of any injury, volunteered to participate in this study. Two dimensional video data were collected at 50 Hz using a MacReflex video system. A backpack and a front pack were compared using loads of 10 and 15% of body weight. Markers were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…It is reasonably well established that distributing load on both the anterior and posterior of the body reduces forward lean during load carriage (Kinoshita, 1985;Harman et al, 1994;Fiolkowski et al, 2006). Kinoshita (1985) suggested that the inclined posture adopted with a backpack system appears to facilitate forward advancement of the body, while the double-pack system inhibits this advancement.…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…It is reasonably well established that distributing load on both the anterior and posterior of the body reduces forward lean during load carriage (Kinoshita, 1985;Harman et al, 1994;Fiolkowski et al, 2006). Kinoshita (1985) suggested that the inclined posture adopted with a backpack system appears to facilitate forward advancement of the body, while the double-pack system inhibits this advancement.…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…A discrepancy between the COM control in different directions was also observed in the study of rapid arm movements, which showed that the pattern of anticipatory trunk muscle activity was consistent with control of the COM in the A/P direction and inconsistent with the COM control in the vertical direction (Hodges et al, 1999). Indeed, the literature reports the trunk or hip angles change in subjects carrying a backpack or front pack relative to changes in the head position or displacements of the COP (Chow et al, 2006;Fiolkowski et al, 2006). It was also described in the literature that the duration of the COP displacement, as well as the EMG activity is affected by the medial-lateral shifts of the COM associated with a leg raising task .…”
Section: Effect Of Changes In the Com Positionmentioning
confidence: 82%
“…Continuing work by the main author is investigating the effects on neck and shoulder musculature of such postural differences. Fiolkowski et al [20] found that there were less hip flexion and forwards head position when the backpack was carried anteriorly. An anterior shift in the centre of gravity of the head elicits the head and neck postural reflexes involving the vestibulocollic [21], cervicocollic [22] and cervical-facet mechanoreceptors.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%